2015
DOI: 10.1007/s15007-015-0911-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel insights into the role of immune cells in skin and inducible skin-associated lymphoid tissue (iSALT)

Abstract: Summarye skin is equipped with serial barriers that provide rapid and e cient protection against external intruders. Beneath the epidermal physical barriers of the stratum corneum and the tight junctions, the integrated immune systems in both the epidermis and the dermis act in a coordinated manner to protect the host.is "immunological" barrier is composed of various cells, including skin-resident cells, such as keratinocytes, dendritic cells, tissue-resident macrophages, resident memory T cells, mast cells, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 109 publications
(118 reference statements)
0
9
0
4
Order By: Relevance
“…During the sensitization phase of the murine DNFB‐induced CHS model, conventional dendritic cells (cDCs), epidermal Langerhans cells, and Langerin + dermal DCs in the skin take up hapten and present it to T cells . In the elicitation phase, repeat exposure of cDCs to hapten leads to inflammation and consequent activation of IFN‐γ–producing CD8α + T cells and other inflammatory cells (eg, neutrophils, M1‐ and M2‐type macrophages) . It was suggested that IL‐17–producing T cells, which also have a potential to produce IL‐22, contributed to exacerbating DNFB CHS responses .…”
Section: Resultsmentioning
confidence: 99%
“…During the sensitization phase of the murine DNFB‐induced CHS model, conventional dendritic cells (cDCs), epidermal Langerhans cells, and Langerin + dermal DCs in the skin take up hapten and present it to T cells . In the elicitation phase, repeat exposure of cDCs to hapten leads to inflammation and consequent activation of IFN‐γ–producing CD8α + T cells and other inflammatory cells (eg, neutrophils, M1‐ and M2‐type macrophages) . It was suggested that IL‐17–producing T cells, which also have a potential to produce IL‐22, contributed to exacerbating DNFB CHS responses .…”
Section: Resultsmentioning
confidence: 99%
“…The molecular detail of underlying mechanism for the dysregulation of paracellular permeability is discussed in other reviews [ 4 ]. In addition to vascular leakage, postcapillary venules can also serve as the specific site of leukocyte infiltration and inflammatory cell gathering, which is essential for immune responses in the skin [ 35 38 ].…”
Section: The Drastic Increase In Vascular Permeability Upon Various Cmentioning
confidence: 99%
“…ИСК представлена клетками как врожденного, так и адаптивного иммунитета. На сегодня к ИСК относят клетки Лангерганса и кератиноциты эпидермиса, обеспечивающие не только формирование механического барьера, но также распознавание патогенов с помощью патоген-распознающих рецепторов (PRRs), а также продукцию антимикробных факторов, цитокинов и хемокинов [1,3]. Представительство клеток, DOI: https://doi.org /10.26641/1997-9665.2016.3.14-18 способных распознавать патогены с помощью PRRs, в подлежащей дерме более сложное и разнообразное.…”
Section: Introductionunclassified
“…Гранулы Бирбека формируются в системе эндосом, имеют форму палочки или теннисной ракетки с поперечной исчерченностью, их образование тесно связано с накопления Лангерина. После получения сигнала о повреждении КЛ активируются, захватывают антиген, а его процессинг сопровождается миграцией КЛ через систему лимфатических сосудов кожи в регионарные лимфатические узлы [3]. Предполагается, что основным эффектом активации КЛ является развитие толерантности через стимуляцию Treg [14].…”
Section: Introductionunclassified
See 1 more Smart Citation